Who heals and how does it cure? Treatment of the disease in a rural community from Ecuador - Jessica Valeria Pasto-Capuz; Judith Inmaculada Francisco Pérez; Manuel Ramón Blanco (Universidad de Alicante, 2019)
Introduction: Traditional medicine is a therapeutic alternative that respects ancestral knowledge and multiculturalism. Objective: To explore the practices used for the cure of diseases in the rural community of San Miguel de Chalata, Ecuador. Methods: A qualitative, hermeneutical research was carried out. A semi-structured interview was answered by 22 older adults living in the community. The discourses were recorded, transcribed and analyzed. Results: Traditional medicine is valued to cure somatic diseases due to its accessibility, low cost and effectiveness. They recognize conventional medicine in the cure of chronic diseases, however, they associate it with prolonged waiting times and discriminatory treatment with the elderly. They use rituals in supernatural diseases, mixing faith, religiosity and assistance of the universal divine power. Conclusions: Traditional and conventional medicine have defined attributions in the collective thought of this community. They approve the power of the healer and respect the scientific knowledge of professional  doctors. The barriers of the conventional system should be studied because of their importance in the use of health services and equality in health.